INNOVATION MANAGEMENT IN COMMERCIAL BANKING: FORMATION, DEVELOPMENT AND DIGITAL TRANSFORMATION AT ALOQABANK JSCB - Sogatova Sarvinoz Izatullayevna; S. Khusanov (TADQIQOTLAR, 2026)
ABSTRACT Background: Digital transformation is reshaping the competitive landscape of the  banking  sector  globally,  including  in  Uzbekistan.  Innovation  management  has become a strategic necessity for commercial banks seeking to sustain competitiveness. Methods:  The  study  employs  SWOT  analysis,  comparative  financial benchmarking, structural-functional analysis, and review of official Aloqabank reports (2021–2026). Frameworks include the Oslo Manual (OECD, 2018), ISO 56000, and international fintech research. Results: Key systemic barriers in Aloqabank's innovation  management were identified:  hierarchical  rigidity,  technological  debt,  limited  AI  integration,  and insufficient digital competency. A multi-pillar improvement model is proposed. Conclusions:  Systematic  development  of  innovation  management  is  a prerequisite  for  Aloqabank's  transformation  into  a  modern  technological  financial platform. The proposed model targets active Zoomrad user growth to 5.5–6.0 million (+51–64%) and CIR reduction to 35–38% by 2027–2028.